THE EFFECT OF QUALITY OF WORK LIFE , LEADERSHIP STYLE, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEES MOTIVATION AT THE FINANCIAL AUDIT AGENCY (BPK) REPRESENTATIVE OF THE PROVINCE OF SOUTH SUMATRA - Edi Sugiyono; Nurul Fitria (SEAN Institute, 2022)
This research examines the influence of Quality Of Work Life, Leadership Style and Organizational Culture on Employee Performance Through Employee Motivation at the Supreme Audit Agency (BPK) RI Representative of South Sumatra Province. The method used is descriptive quantitative statistical tools Structural Equation Modeling (SEM). The results of the research concluded that Quality of Work Life, Leadership Style and Organizational Culture have a positive and significant effect on Employee Motivation. Quality of Work Life and Leadership Style have a negative and insignificant effect on employee performance. Organizational culture has a positive and insignificant effect on employee performance. Employee motivation has a positive and significant effect on employee performance. Employee motivation is able to mediate the influence of Quality Of Work Life, Leadership Style and Organizational Culture positively and significantly on Employee Performance.